2020
DOI: 10.1371/journal.pone.0238798
|View full text |Cite
|
Sign up to set email alerts
|

Mesopolysaccharides: The extracellular surface layer of visceral organs

Abstract: The mesothelium is a dynamic and specialized tissue layer that covers the somatic cavities (pleural, peritoneal, and pericardial) as well as the surface of the visceral organs such as the lung, heart, liver, bowel and tunica vaginalis testis. The potential therapeutic manipulation of visceral organs has been complicated by the carbohydrate surface layer-here, called the mesopolysaccharide (MPS)-that coats the outer layer of the mesothelium. The traditional understanding of MPS structure has relied upon fixatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 47 publications
(60 reference statements)
1
17
0
Order By: Relevance
“…The serosal surface of the bowel wall is covered with a serosal MPS. We have recently demonstrated that the MPS is 1000-times thicker than previously assumed—over 10 μm in thickness [ 24 ]. Moreover, high resolution imaging indicates that the serosal MPS demonstrates a branched-chain structure that mirrors the chain structure of pectin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The serosal surface of the bowel wall is covered with a serosal MPS. We have recently demonstrated that the MPS is 1000-times thicker than previously assumed—over 10 μm in thickness [ 24 ]. Moreover, high resolution imaging indicates that the serosal MPS demonstrates a branched-chain structure that mirrors the chain structure of pectin.…”
Section: Discussionmentioning
confidence: 99%
“…The samples were stained and processed as previously described using ruthenium red [ 24 ]. Briefly, samples were stained with ruthenium red (Sigma-Aldrich, Steinheim, Germany) while in 1% glutaraldehyde, then further processed with the rOTO protocol before embedding in Epon (Serva, Heidelberg, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of surgical techniques, including pleural flaps [ 40 ] and pleural tents [ 6 ], have been designed to facilitate the healing of pleural injures. Due to the structural biosimilarity of pectin and the pleural glycocalyx [ 41 ], we speculate that pectin may have a similar function in facilitating visceral pleural repair.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that HPF immobilizes cellular structures in their near-native form within milliseconds and that subsequent dehydration and contrasting by FS allows for the preservation of ultrastructure and antigenicity due to a gradual temperature rise that successively replaces amorphous ice with organic solvents [ 10 , 22 ]. HPF/FS has recently been successfully applied to visualize the interaction of magnetic nanoparticles with the GCX of THP-1 cells during initial contact [ 9 ] and the extracellular surface layer of visceral organs [ 23 ].…”
Section: Discussionmentioning
confidence: 99%